2018
DOI: 10.1111/jphp.12897
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics studies of 4′-cyano-2′-deoxyguanosine, a potent inhibitor of the hepatitis B virus, in rats

Abstract: The data generated in this study provide support for the clinical development of CdG for use in the treatment of HBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…ConA-induced VLI model rats were intravenously (n = 4) or orally (n = 4) administered a single injection of CdG (1 mg/kg), which was synthesized as reported previously. 5) Blood samples (250 µL) were collected from the femoral vein using a heparinized syringe at 3, 15, 30, 45, 60, 90 and 180 min after intravenous administration and at 5, 15, 30, 45, 60, 90 and 180 min after oral administration. The blood samples were centrifuged at 3,000 rpm for 10 min to obtain plasma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ConA-induced VLI model rats were intravenously (n = 4) or orally (n = 4) administered a single injection of CdG (1 mg/kg), which was synthesized as reported previously. 5) Blood samples (250 µL) were collected from the femoral vein using a heparinized syringe at 3, 15, 30, 45, 60, 90 and 180 min after intravenous administration and at 5, 15, 30, 45, 60, 90 and 180 min after oral administration. The blood samples were centrifuged at 3,000 rpm for 10 min to obtain plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has searched for novel NAs with antiviral activity against not only wild-type HBV but also HBV that is resistant to the currently marketed NA preparations. 4,5) As a result of screening of over 100 NAs in a real-time HBV-PCR assay, we identified a candidate compound, 4′-cyano-2′deoxyguanosine (CdG, Chart 1), which showed superior antiviral activity against ADV-resistant HBV (HBV A181T/N236T ) and ETV-resistant HBV (HBV L180M/S202G/M204V ) to ADV and ETV, respectively. 4) In addition, a study of the pharmacokinetics of CdG in healthy rats showed that CdG possessed favorable pharmacokinetic properties for use as an oral NA preparation against HBV infections with good bioavailability and a high distribution to the liver.…”
Section: Introductionmentioning
confidence: 99%
“…The use of substituent that has an ethynyl (−CCH) or cyano (−CN) group added to the ribose ring of an NRTI has been used in compounds other than EFdA (Figure ): a similar approach inspired the design of HBV NRTIs that have a 4′-cyano and are expected to act by a similar mechanism of inhibition (Figure ). , In addition, remdesivir, a related compound with a 1-ethynyl substitution on the ribose ring, has been introduced as a potent RNA-dependent RNA polymerase inhibitor of Ebola and recently approved as the first antiviral against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2, COVID-19) (Figure ). Hence, compounds that act by unique and multiple mechanisms of action may be able to maintain antiviral activity if only a single of their mechanism of action is reversed.…”
Section: Strategies To Avoid Drug Resistancementioning
confidence: 99%
“…
Fig. 4 Selected antiviral nucleoside derivatives currently tested in preclinical or clinical trials [ [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] ].
…”
Section: Nucleoside Analoguesmentioning
confidence: 99%